The Effect Of Work Discipline Leadership and Work Loyalty On Employee Performance at the South Bengkulu Health Office - Muhammad Iqbal; Marliza Ade Fitri (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the influence of leadership style, work discipline, and work performance loyalty of employees at the South Bengkulu Health Office. This type of research is quantitative research. The sample in this study were 30 employees at the South Bengkulu Health Office. Data collection techniques were observation, documentation and questionnaires. The processed data was analyzed using the SPSS 25 formula. Based on the results of partial simultaneous research, there is an influence between leadership style, work discipline and loyalty on employee performance at the South Bengkulu Health Office and it can be seen from the results of the study that 66.1% of employee performance is influenced by leadership style, work discipline and loyalty.